LC–MS/MS method for simultaneous determination of flavonoids and physalins in rat plasma: Application to pharmacokinetic study after oral administration of Physalis alkekengi var. franchetii (Chinese lantern) extract. (2nd May 2017) - Guo, Yaqing; Liu, Hongxia; Ding, Liqin; Oppong, Mahmood; Pan, Guixiang; Qiu, Feng
Abstract: A rapid and sensitive liquid chromatography with tandem mass spectrometry (LC‐MS/MS) method was developed and validated for the simultaneous determination of luteolin, luteolin‐7‐ O ‐ β ‐D‐glucopyranoside, physalin A, physalin D and physalin L in rat plasma. Scutellarein and dexamethasone were used as the internal standards (IS). Plasma samples were prepared by liquid‐liquid extraction with ethyl acetate. The five constituents were separated on an Acquity UPLC BEH C18 column (100 mm × 2.1 mm, 1.7 μm). A gradient elution procedure was used with acetonitrile (A)‐0.1% aqueous formic acid (B). Mass spectrometric detection was performed in negative ion multiple reaction monitoring mode with an electrospray ionization (ESI) source. This method showed good linearity ( r 2  > 0.997) over a concentration range of 2.0–500 ng/mL with a lower limit of quantification of 2.0 ng/mL for all five compounds. The inter‐ and intra‐day accuracy ranged from 91.7 to 104%, and precisions (RSD) were <6.46% for all analytes. The extraction recoveries of all analytes were >85%. This validated method was successfully applied for the first time to the pharmacokinetic study of five ingredients after oral administration of 70% ethanol extract of Chinese lantern in rats.